Tailoring the internal structure of liquid crystalline nanoparticles responsive to fungal lipases : A potential platform for sustained drug release - Poletto, F. S.; Lima, F. S.; Lundberg, D.; Nylander, T.; Loh, W. (Colloids and Surfaces B: Biointerfaces, 2016)
Lipases are key components in the mechanisms underlying the persistence and virulence of infections by fungi, and thus also promising triggers for bioresponsive lipid-based liquid crystalline nanoparticles. We here propose a platform in which only a minor component of the formulation is susceptible to cleavage by lipase and where hydrolysis triggers a controlled phase transition within the nanoparticles that can potentially allow for an extended drug release. The responsive formulations were composed of phytantriol, which was included as a non-cleavable major component and polysorbate 80, which serves both as nanoparticle stabilizer and potential lipase target. To monitor the structural changes resulting from lipase activity with sufficient time resolution, we used synchrotron small angle x-ray scattering. Comparing the effect of the two different lipases used in this work, lipase B from Candida Antarctica, (CALB) and lipase from Rhizomucor miehei (RMML), only CALB induced phase transition from bicontinuous reverse cubic to reverse hexagonal phase within the particles. This phase transition can be attributed to an increasing amount of oleic acid formed on cleavage of the polysorbate 80. However, when also a small amount of a cationic surfactant was included in the formulation, RMML could trigger the corresponding phase transition as well. The difference in activity between the two lipases can tentatively be explained by a difference in their interaction with the nanoparticle surface. Thus, a bioresponsive system for treating fungal infections, with a tunable selectivity for different types of lipases, could be obtained by tuning the composition of the nanoparticle formulation.